Being Dead Otherwise - Allison, Anne (Duke University Press, 2023)
With an aging population, declining marriage and childbirth rates, and a rise in single households, more Japanese are living and dying alone. Many dead are no longer buried in traditional ancestral graves where their descendants would tend their spirits and individuals are increasingly taking on mortuary preparation for themselves. In Being Dead Otherwise Anne Allison examines the emergence of new death practices in Japan as the old customs of mortuary care are coming undone. She outlines the new proliferation of industries, services, initiatives, and businesses that offer alternative means for tending to the dead, ranging from automated graves, collective gravesites, and crematoria to one-stop mortuary complexes and robot priests. These new burial and ritual practices provide alternatives to the long-standing traditions of burial and commemoration of the dead. In charting this shifting ecology of death, Allison outlines the potential of these solutions to radically reorient sociality in Japan in ways that will impact how we think about death, identity, tradition, and culture in Japan and beyond
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Mai 2023)
Keywords: SOCIAL SCIENCE / Anthropology / Cultural & Social; Death care industry -- Japan; Death -- Social aspects -- Japan; Funeral rites and ceremonies -- Japan